Nurses’ Job Satisfaction in Respiratory Isolation Units of Coronavirus Disease - Hussein, Zahraa (Iraqi National Journal of Nursing Specialties, 2022)
Abstract Objective(s): To assess the job satisfaction during of covid-19 among the nurses in respiratory isolation units of coronavirus disease. Methodology: A descriptive cross-sectional design was carried out in four hospitals at isolation units of coronavirus disease from the period (21th December, 2021 to 27th January, 2022). A non-probability (convenience) sampling method consists of (300) nurse was selected convenience based on the study criteria. The tool used to measure the job satisfaction is Job satisfaction scale for clinical nursing (JSS-CN). This tool consists of two parts, the first part is for demographic information and consists of 8 items, and the second part is a measure of job satisfaction for clinical nurses of 33 items. Data were entered into IBM-SPSS, version 23, and analyzed using descriptive statistics by specifying: frequencies, percentages, and arithmetic mean. Results: presented that nurses’ job satisfaction were within high score in all items because the mean more than (3.18). Conclusion: Job satisfaction levels for nurses working in isolation units were not affected by COVID-19 as its levels were high. Recommendations: The study recommends maintaining levels of job satisfaction for nurses within the current levels by providing psychological support and continuous encouragement by nursing officials in order to continue the nursing giving at its best during the epidemic period.